THE EFFECT OF PICTURE AND PICTURE COOPERATIVE LEARNING MODEL WITH THE ASSISTANCE OF FLASHCARD MEDIA ON STUDENTS' LEARNING OUTCOMES AT SMA NEGERI 3 WAINGAPU - Yosiana Ana Hamu; Vidriana Oktoviana Bano; Yohana Ndjoeromana (Universitas Labuhanbatu, 2023)
This study aims to determine the effect of the cooperative learning model type picture and picture assisted by flashcard media on students' biology learning outcomes in the subject of the human excretory system. This study is a quasi-experimental study, with a pretest-posttest control group design. The sample in this study was class XI MIPA2 (experimental class) using the picture and picture type cooperative learning model assisted by flashcard media and XI MIPA3 (control class) using the conventional learning model. The sampling technique used is purposive sampling, conducted at SMA N 3 Waingapu, even semester, Academic Year 2022/2023. The research instruments were in the form of documentation and a written test of 50 multiple choice questions, consisting of 10 pretest questions and 15 posttest questions which were conducted in 2 meetings. The research data were analyzed using statistical tests, namely the Validity test, Reliability test, Normality test, Homogeneity test, t test (paired sample t test) using SPSS version 22. Based on the results of the analysis, the average posttest value for the experimental class was 77.70 and the control 55.2. The results of hypothesis testing with paired samples t test obtained sig (2-tailed) <0.05 (0.00 <0.05). This shows that there is an effect of using the picture and picture type cooperative learning model assisted by flashcard media on the biology learning outcomes of class XI students.